2017
DOI: 10.21608/jssae.2017.37537
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Planting Methods, Irrigation Techniques and Weed Control Treatments in Wheat Crop Performance, Associated Weeds and Water Productivity

Abstract: A field trial was executed at Gemmeiza during 2014/2015 and 2015/2016 winter seasons. The experiment aiming at finding the response of wheat crop and the associated weeds to planting methods vis Raised Bed Broadcasting (RBB), Flat in Rows (FR) and Flat Broadcasting (FB), irrigation techniques (irrigating as 40, 60 and 80% of available soil moisture were depleted) and weeding treatments (Pallas, Atlantis, Brominal w + Topik, Hand weeding and Un-weeded (Control) as well as their interactions. The crop-water rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The weeds cause extra competition of crop plants with biotic factors of the environment. The large population of weeds cause drought to the crop plants as more moisture is taken which ultimately caused damage to crop plants, (Ali et al,2012 andBadawi, andKenapar 2017) so, choose the highyielding ability genotypes is very important to raise wheat productivity per unit of area and suppression weed growth. So, the main objective of the current study is to investigate the effect of deficit irrigation and weed control treatment on growth, yield, yield components, and productivity of irrigation water on some wheat genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…The weeds cause extra competition of crop plants with biotic factors of the environment. The large population of weeds cause drought to the crop plants as more moisture is taken which ultimately caused damage to crop plants, (Ali et al,2012 andBadawi, andKenapar 2017) so, choose the highyielding ability genotypes is very important to raise wheat productivity per unit of area and suppression weed growth. So, the main objective of the current study is to investigate the effect of deficit irrigation and weed control treatment on growth, yield, yield components, and productivity of irrigation water on some wheat genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Majeed et al (2015) pointed out that in bed planting method, increasing N up to 120 kg ha −1 excessed wheat yield up to 5.12 t ha −1 , compared with the yield at the same N fertilizer rate (4.45 t ha −1 ) in flat planting method. Badawi and Kenapar (2017) revealed that it is suitable to irrigating wheat at 80% of available soil moisture depletion when cultivation it on raised beds. This study aims to evaluate the effect of changing wheat planting pattern on sowing grain on lines or raised bed compared to sowing in basins (flat broadcasting).…”
Section: Introductionmentioning
confidence: 99%